Warren And Cantu, Eds., History Education 101: The Past, Present, And Future Of Teaching Preparation - Marsh, Dawn (Teaching History: A Journal of Methods, 2010)
This volume of thirteen essays explores the current state of history education for pre-service teachers. Warren and Cantu divide the essays into three sections: "Context," "Practice," and "New Directions." For educators and academics who share in the education of pre-service history teachers, the topics explored in this collection are, unfortunately, all too familiar. Despite the resurgence of attention paid to the education of history teachers that began in the late eighties and reached its greatest pubic attention with the publication of the National Standards for History in the mid-1990s, it appears there is less interest or investment by academia in this issue now than ever before.